Pengaruh Self Determination terhadap Work Engagement pada Mahasiswa ITS yang Mengikuti Magang - Putri Allya Syafira; M. Ilmi Hatta (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The Minister of Education and Culture (Kemendikbud) held an internship program called MBKM Kampus Merdeka: Program Magang Kampus Merdeka. The purpose of this program is to seek and increase knowledge in any various companies while improving soft skills. This must be accompanied by motivation from individuals so they can try to work harder and want to involved with their works. So therefore, an internship students must have a high self determination and work engagement. The author took an 87 sample from ITS Student who took an internship by Program Magang Kampus Merdeka. Author using The Convenience Sampling as the sampling technique. The measurement tools for Self Determination using the Basic Need Satisfaction at Work developed by Deci, et.al (2001) which has been adapted into Bahasa Indonesia by Rhadiatullah (2016). The measurement tools for Work Engagement using the Utrecht Work Engagement Scale-17 (UWES-17) developed by Schaufeli & Bakker (2004) which has been adapted into Bahasa Indonesia by Risma, et al (2021). The final results using the Simple Linear Regression Test shows the score is 0,004, which mean the value is less than 0,05. The conclusion for this research is that the Self Determination has an influence on Work Engagement. Abstrak. Kemendikbud mengadakan program magang yang Bernama MBKM Kampus Merdeka: Program Magang Kampus Merdeka. Tujuannya adalah untuk mencari dan meningkatkan pengetahuan di berbagai perusahaan, selain itu juga untuk meningkatkan soft skill. Hal ini harus dibarengi dengan motivasi dari individu sehingga mereka bisa bekerja lebih giat dan dapat terlibat dengan pekerjaannya. Maka dari itu, mahasiswa magang harus memiliki self determination dan work engagement. Peneliti mengambil 87 sampel dari Mahasiswa ITS yang mengikuti Program Magang Kampus Merdeka. Peneliti menggunakan Teknik Convenience Sampling. Alat ukur yang digunakan untuk Self Determination adalah Basic Needs Satisfaction at Work yang dikembangkan oleh Deci, et al (2001) yang telah diadaptasi ke dalam Bahasa Indonesia oleh Rhadiatullah (2016). Alat ukur yang digunakan untuk Work Engagement adalah Utrecht Work Engagement Scale-17 yang dikembangkan oleh Schaufeli & Bakker (2004) yang telah diadaptasi ke dalam Bahasa Indonesia oleh Risma, et al (2021). Hasilnya dengan menggunakan Uji Regresi Linear Sederhana menunjukkan hasil 0,004, yang artinya nilai tersebut lebih kecil dari 0,05. Kesimpulannya adalah Self Determination memiliki pengaruh terhadap Work Engagement.